Molecular characterization of methicilin-resistant Staphylococcus aureus strain BM85 isolated from a Vietnamese patient with bloodstream infection: MRSA strain BM85 resistant to multiple antibiotics - Dinh Phuc, Hoang; Thanh Tam, Tran Thi; Thu Hang, Le Thi; Kieu Oanh, Nguyen Thi; Hai Long, Vu Dang; Duy Hung, Kieu; Bañuls, Anne-Laure; Quang Huy, Nguyen (Vietnam Journal of Biotechnology, 2023)
Methicillin-resistant Staphylococcus aureus (MRSA) is a threat to global health due to its resistance to β-lactam antibiotics and many other antibiotic classes developed via both intrinsic and acquired mechanisms. In this study, molecular characteristics related to antibiotic resistance of MRSA strain BM85 were investigated by whole-genome sequencing of a sample isolated from a patient with bloodstream infection at Bach Mai Hospital, Vietnam. Antibiotic susceptibility testing was also performed to determine the correlation between the presence of antibiotic-resistant genes and resistance phenotypes. Genomic analyses showed that the MRSA strain BM85 belonged to the major community-acquired (CA)-MRSA lineage ST59 originating from Taiwan. The strain harbored Staphylococcal Cassette Chromosome mec (SCCmec) type Vb (5C2&5) and Panton-Valentine leukocidin (PVL). Additionally, MRSA strain BM85 also possessed various antibiotic-resistant genes including tet38, tetK, blaZ, mecA, aph(3')-IIIa, aacA-aphD, and ermB which were located on mobile genetic elements  MESPM1, Tn553-Tn4001 transposon, and a plasmid carrying the tetK gene, which was responsible for tetracycline resistance. The genotypic-resistant results were concordant with the phenotypic-resistant profile in which MRSA strain BM85 was resistant to penicillin, cefoxitin, gentamicin, kanamycin, tobramycin, erythromycin, and tetracycline. The sequencing data for the MRSA strain BM85 was deposited in GenBank, NCBI under accession number: BioProject PRJNA857185. In conclusion, the acquisition of the foreign genetic elements associated with antibiotic resistances through horizontal gene transfer mechanisms was the key driver of multidrug resistance in the multidrug-resistant MRSA strain BM85.